Barriers to Providing Prehospital Care to Ischemic Stroke Patients: Predictors and Impact on Care. Issue 5 (29th August 2018) - Li, Timmy; Cushman, Jeremy T.; Shah, Manish N.; Kelly, Adam G.; Rich, David Q.; Jones, Courtney M. C.
Abstract: Introduction: Ischemic stroke treatment is time-sensitive, and barriers to providing prehospital care encountered by Emergency Medical Services (EMS) providers have been under-studied. Hypothesis/Problem: This study described barriers to providing prehospital care, identified predictors of these barriers, and assessed the impact of these barriers on EMS on-scene time and administration of tissue plasminogen activator (tPA) in the emergency department (ED). Methods: A retrospective cohort study was performed using the Get With The Guidelines-Stroke (GWTG-S; American Heart Association [AHA]; Dallas, Texas USA) registry at two hospitals to identify ischemic stroke patients arriving by EMS. Variables were abstracted from prehospital and hospital medical records and merged with registry data. Barriers to care were grouped into themes. Logistic regression was used to identify predictors of barriers to care, and bi-variate tests were used to assess differences in EMS on-scene time and the proportion of patients receiving tPA between patients with and without barriers. Results: Barriers to providing prehospital care were documented for 15.5% of patients: 29.6% related to access, 26.7% communication, 23.0% extrication and transportation, 20.0% refusal, and 14.1% assessment/management. Non-white and non-black race (OR: 3.69; 95% CI, 1.63-8.36) and living alone (OR: 1.53; 95% CI, 1.05-2.23) were associated with greater odds of barriers to providing care. The EMS on-scene time was ≥15 minutes for 70.4% of patients who had a barrier to care, compared with 49.0% of patients who did not (P<.001). There was no significant difference in the proportion of patients who were administered tPA between those with and without barriers to care (14.1% vs 19.2%; P=.159). Conclusions: Barriers to providing prehospital care were documented for a sizable proportion of ischemic stroke patients, with the majority related to patient access and communication, and occurred more frequently among non-white and non-black patients and those living alone. Although EMS on-scene time was longer for patients with barriers to care, the proportion of patients receiving tPA in the ED did not differ. T Li, JT Cushman, MN Shah, AG Kelly, DQ Rich, CMC Jones .Barriers to providing prehospital care to ischemic stroke patients: predictors and impact on care .Prehosp Disaster Med. 2018 ;33 (5 ):501 –507 .